Living with chronic diseases in long term: from vulnerabilities to fragility - Maia, M. (5th World Conference on Qualitative Research, 2021)
Chronic diseases such as HIV infection or diabetes increases the risk of developing comorbidities earlier than the general population. In turn, it can anticipate the onset of disability and increase a social and psychological vulnerability. Aging also tends to be linked to social vulnerability, and situations of discrimination. Aging, disease and discrimination can lead to a deteriorated identity, discredit and isolation, which can increase people's fragility, understood as a multidimensional entity that includes the physical, physiological, psychological and social dimensions. The research on people living with HIV was conducted in France, and coordinated by Rommel Mendes-Leite. Data collection was carried out in 2013 at three hospitals in the Lyon region, where 45 peoples, women and men aged 50 years or more were interviewed. Data analysis followed the Grounded Theory method. The research on people living with type 1 and type 2 diabetes was conducted by me in Lisbon, Portugal, in a hospital and in a health center. I conducted 30 semi-directive interviews between 2018 and 2020. A content analysis was carried out, following the Grounded Theory. Looking at the results, there are several points in common, related to the issues of limitations and suffering caused by chronic diseases and aging: social isolation, impoverishment, the importance of medical monitoring and relationships with professionals health, and the therapeutic management needed in long-term illnesses. The management of chronic diseases is linked to the: socioeconomic status, education level, living environment, gender, place of residence, etc. These factors have varying importance depending on the baggage of values, beliefs and knowledge each individual carry. The result is a set of representations and ways of doing that have a subjective side but that are also defined by the context of life.